Total quality management in small and medium enterprises Prospects and challenges - Guerroumi, Hamid; Mazouz, Hayat (Dirassat Journal Economic Issue, 2017)
SME’s are considered the main engine of the economy of any country, given the large contribution to economic growth and increase national output and reduce unemployment, but which has become a concern for owners and managers of these institutions is intense competition faced by these institutions, whether at the local or global level that has become threaten its survival and it continues to operate, so it was incumbent on them to adopt new management concepts able to increase the competitiveness of these institutions, which come in the forefront of the overall quality, which is the entrance of each improvement operations and development management of the institution.